2022
DOI: 10.1002/advs.202202116
|View full text |Cite
|
Sign up to set email alerts
|

Epstein–Barr Virus‐Encoded MicroRNA‐BART18‐3p Promotes Colorectal Cancer Progression by Targeting De Novo Lipogenesis

Abstract: The Epstein–Barr virus (EBV) genome encodes a cluster of 22 viral microRNAs, called miR‐BamHI‐A rightward transcripts (miR‐BARTs), which are shown to promote the development of cancer. Here, this study reports that EBV‐miR‐BART18‐3p is highly expressed in colorectal cancer (CRC) and is closely associated with the pathological and advanced clinical stages of CRC. Ectopic expression of EBV‐miR‐BART18‐3p leads to increased migration and invasion capacities of CRC cells in vitro and causes tumor metastasis in vivo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 81 publications
0
5
0
Order By: Relevance
“…A tumor is formed by the abnormal proliferation of cells due to the loss of normal regulation of local tissue cells at the gene level under the action of various tumorigenic factors, such as viruses, pollution, tobacco, alcohol, and chemical carcinogens, 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 which is attributed to the action of these factors in stimulating or inactivating key signaling pathways and genes, such as the phosphoinositide 3‐kinase (PI3K)/AKT, Wnt/β‐catenin, Ras/extracellular signal‐regulated kinase (ERK), nuclear factor kappa B (NF‐κB), phospholipase C gamma (PLCγ), sting, signal transducer and activator of transcription (STAT), fibroblast growth factor (FGF)/fibroblast growth factor receptor (FGFR), c‐Myc, p53, and so on. 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 Among them, the FGF/FGFR pathway plays a significant role in maintaining normal physiological balance of the human body.…”
Section: Introductionmentioning
confidence: 99%
“…A tumor is formed by the abnormal proliferation of cells due to the loss of normal regulation of local tissue cells at the gene level under the action of various tumorigenic factors, such as viruses, pollution, tobacco, alcohol, and chemical carcinogens, 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 which is attributed to the action of these factors in stimulating or inactivating key signaling pathways and genes, such as the phosphoinositide 3‐kinase (PI3K)/AKT, Wnt/β‐catenin, Ras/extracellular signal‐regulated kinase (ERK), nuclear factor kappa B (NF‐κB), phospholipase C gamma (PLCγ), sting, signal transducer and activator of transcription (STAT), fibroblast growth factor (FGF)/fibroblast growth factor receptor (FGFR), c‐Myc, p53, and so on. 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 Among them, the FGF/FGFR pathway plays a significant role in maintaining normal physiological balance of the human body.…”
Section: Introductionmentioning
confidence: 99%
“…BART miRNAs have been shown to have potential roles involving cancer growth, tumor invasion, evasion of host immune surveillance, and lipid metabolism. For example, BART1-3p can target and inhibit E2F3 thereby inducing cell cycle arrest and inhibiting cell growth in gastric cancer cells ( 43 ); BART13 promotes NPC cell growth and metastasis by targeting the NKIRAS2/NF-κB pathway and thereby promoting NPC cell growth and metastasis ( 44 ); BART8-3p targets the inhibition of RNF38 to promote NPC metastasis ( 29 ); BART6-3p inhibits EBV-triggered interferons-β response and promotes EBV infection by targeting the 3′UTR of retinoic acid-inducible gene I mRNA ( 45 ); BART18-3p can regulate de novo adipogenesis to promote colorectal cancer progression, and so on ( 46 ). Previous studies have shown that BART2-5p can target and inhibit Rho family GTPase 3 and activate Rho signaling to enhance tumor cell motility ( 47 ).…”
Section: Discussionmentioning
confidence: 99%
“…FASRL enhances fatty acid synthesis and lipid accumulation by binding to the fatty acid synthesis rate-limiting enzyme acetyl coenzyme A carboxylase (ACAC), thereby promoting hepatocellular carcinoma (HCC) [ 119 ]. A study has revealed that miR-BART18-3p, encoded by EBV, activates the HIF-1α/LDHA axis by targeting sirtuin to promote lactate accumulation and acetyl coenzyme A production under hypoxic conditions, resulting in enhanced acetylation of histones H3K9, H3K14 and H3K27 of fatty acid synthase (FASN) and activates de novo synthesis of fat [ 120 ]. Accumulated research has proved that dysregulated ncRNAs play an indispensable role in regulating lipid metabolism.…”
Section: Ncrnas Affect Cancer Progression Through Metabolic Reprogram...mentioning
confidence: 99%